The psychological impact of long bone fractures in KwaZulu-Natal, South Africa: A cross-sectional study - Sevani Singaram; Mergan Naidoo (AOSIS, 2020)
Background: Long bone fractures are known to cause a decline in quality of life due to loss of physical functioning. Loss of independence due to loss or decline of physical functioning can also cause poorer psychological health. There is limited data on depression among orthopaedic patients in South Africa. Methods: The validated Patient Health Questionnaire-9 depression scale was used to establish patient reported outcomes. The Chisquare or Fishers exact test was used where appropriate to compare the various psychological variables and the impact from upper and lower extremity sites. The Kruskal Wallis test was used to test differences in the overall depression score between subgroups. Univariate and multivariate linear regression was used to assess the relationship between variables of interest and the overall depression score, while adjusting for age and gender. Results: A total of 821 research participants completed the questionnaire. The overall depression score in patients with a fracture ranged from 0 to 23 with a mean of 8.26 and a standard deviation of 4.76. The majority of participants (37.64%) had depression scores ranging from 5 to 9 which is associated with mild depression.